Women in STEM Education and Employment: Insights from University Students in Morocco - Benmassoud , Jihane; Bouchara, Aicha (Utamax : Journal of Ultimate Research and Trends in Education, 2023)
Worldwide, women represent 35% of all students enrolled in science, technology, engineering, and mathematics (STEM) fields. In Morocco, 42.2% of women are engineering graduates. This study aims to investigate university students’ attitudes, experiences, and awareness about men and women in STEM education and employment. An online questionnaire was adopted to collect both quantitative and qualitative data. Using convenient sampling, 181 STEM university students participated in this study from four different institutions in Morocco which are: Faculty of Sciences and Techniques in Tangiers, The School of Technology in Essaouira, Hassan II Institute of Agronomy and Veterinary Sciences in Rabat, and the Higher School of Technical Education in Mohammadia. The findings show that the majority of students (83.2%) do not perceive the STEM fields as typically masculine. A minority (6.7%) believes that some professors behave differently with male and female students. Moreover, most respondents (55.6%) were not aware of the underrepresentation of women in STEM fields and were unable to recognize the importance of their contributions to fixing society’s challenges. This study, therefore, is relevant for decision makers in higher educational institutions to reconsider the methods and contents of STEM education in order to enhance a gender responsive pedagogy